Full-Length Transcriptome of the Whale Shark (Rhincodon typus) Facilitates the Genome Information - Lou, Fangrui; Wang, Li; Wang, Zhiyang; Wang, Lei; Zhao, Linlin; Zhou, Qingjie; Lu, Zhichuang; Tang, Yongzheng (Frontiers in Marine Science, 2022)
Rhincodon typus is a keystone and indicator species in marine ecosystems. Meanwhile, R. typus has been listed on the IUCN red list of vulnerable species. Here we used ONT platform to determine the full-length (FL) transcriptome of R. typus and obtained 14,930 FL transcripts. Among all FL transcripts, 14,915 transcripts were covered 11,892 genetic loci and 1,642 novel genetic loci were futher found. Meanwhile, we identified 714 novel transcripts by compared FL transcripts with the R. typus genome. Based on FL transcripts, we also predicted the distribution patterns of ASs, LncRNAs, polyAs, CDSs and methylation sites on FL transcriptome of R. typus. Furthermore, a total of 31,021 (97.86%) CDSs can obtained annotation information. Overall, our work firstly provided the FL transcriptome and these sequences complete the annotated R. typus genome information. Furthermore, these information are a potential resource to study biological processes of R. typus.